Design and fabricate mini biogas digester - Ahmad Aizad, Jamil (2010)
This project is about designing and fabricate the mini biogas digester to fermentation of waste product in order to produce and collect methane gas. Nowadays, people know that the methane that not only cheap in price, but has many advantages such as to replace cooking gas and to generate electricity. To produce and collect the methane gas, they need a biogas digester that usually bigger in size, but the people need a biogas digester that suitable to use at home and portable. So, based on the objective for this project is in order to help them, a mini biogas digester is designed by considering the ergonomic factors for the people use. After the designing complete, it is needed to be transform into the real product. The materials that used to fabricate this product are selected, and they are round hollow steel, square hollow steel, sheet mild steel and wood. The processes involved are welding, drilling, and grinding, riveting, fastening and using glue to assemble all the parts. This project design is generated by using the other current biogas digester and do the comparisons between them, then make the new concept to make it more portable and user friendly compared to the current product.